Parecoxib Shortens the Duration of Acute Postoperative Pain After Laparoscopic-Assisted Vaginal Hysterectomy - Yang, Shuyi; Xiao, Wei; Wang, Shijun; Meng, Lingzhong; Zhou, Liane; Wan, Anxia; Liu, Yang; Feng, Shuai; Wang, Tianlong (Frontiers in Pharmacology, 2019)
The effect of parecoxib sodium on the duration and severity of acute postoperative pain after laparoscopic-assisted vaginal hysterectomy has been inadequately studied. This randomized, controlled trial compared the effects of parecoxib, methylprednisolone, and placebo on the duration of acute postoperative pain after elective laparoscopic-assisted vaginal hysterectomy. Ninety-four eligible patients were randomized to three groups (parecoxib sodium 40 mg [Group P], methylprednisolone 1 mg/kg [Group M], and saline [Group S]). The duration of pain during coughing (median [interquartile range]) was significantly lower in Group P than in Group M or Group S (26.0 [5.8–48.0] vs. 48.0 [30.0–55.5] vs. 48.0 [36.0–58.5] h; p = 0.025). The duration of pain during rest was also significantly lower in Group P than in Group M or Group S (5.5 [3.8–21.0] vs. 24.0 [6.0–28.0] vs. 22.0 [5.8–36.0] h; p = 0.009). Compared with those in Group M and Group S, the patients in Group P reported less intense visceral pain during coughing at 12 (p = 0.050) and 24 h (p = 0.009) as well as at rest at 12 h (p = 0.008). Compared with those in Group P and Group S, the patients in Group M showed lower serum C-reactive protein levels and higher blood glucose levels after surgery. No differences were noted in nausea, vomiting, length of hospital stay, wound infection, and delayed wound healing among the groups. Thus, parecoxib sodium reduces the duration and intensity of acute postoperative pain after laparoscopic-assisted vaginal hysterectomy.